Preparation and properties of carbon-nanotube composites with natural rubber and epoxidized natural rubber - Kummerlöwe, C.; Vennemann, N.; Pieper, S.; Siebert, A.; Nakaramontri, Y. (Polimery, 2014)
Composites of carbon-nanotubes (CNTs) and natural rubber (NR), as well as epoxidized natural rubber (ENR), were prepared by melt compounding in an internal mixer. The state of CNT dispersion was determined by examination of the electrical percolation threshold of the composites. The composites with the more polar ENR exhibit a lower percolation threshold than those with NR matrices. It was also shown that two-step processing using an internal mixer and two roll mill resulted in a better CNT dispersion and lower percolation threshold. The effect of CNTs on vulcanization and crosslinking were investigated by oscillating rheometer and DSC measurements. The crosslink densities of the composites were determined by equilibrium swelling measurements as well as hysteresis tensile tests. A significant increase in crosslink densities of the composites with increasing CNT content was detected. Increasing CNT content also resulted in accelerated crosslinking reaction. The thermal conductivity of the composites was tested by DSC measurements. Avery large increase of thermal conductivity could be obtained with a low CNT content. However, it turned out that the increase of thermal conductivity is restricted by the thermal resistance at the interface between CNTs and the matrix.